نشأة اللغة العربية وتطورها فى التاريخ الإسلامي - Darwin Zainuddin (Universitas Islam Negeri Sumatera Utara Medan, 2022)
Arabic is a language that contributes vocabulary to languages that exist in the world, the main reason is that this language is used in the holy book, namely al-Qur'an which has survived in its original language for more than 14 centuries. Arabic is one of the Samiyah language families, ascribed to the son of the Prophet Noah named Sam ibn Nuh, then Arabic moved to